Ultrasound-guided percutaneous transhepatic cholecystic puncture and drainage for acute severe cholecystitis—a Case Report - Liqiang Li; Liqiang Li; Yunfei Zhang; Yunfei Zhang; Zihan Zeng; Zihan Zeng; Liang Li; Liang Li; Jun Zhang; Jun Zhang (Frontiers in Medicine, 2025)
BackgroundPatients with multiple underlying diseases, older patients, or those with temporary contraindications to surgery should not undergo laparoscopic cholecystectomy for the time being. Instead, percutaneous transhepatic cholecystic puncture and drainage with tube placement is the preferred option.Patient summaryA 55-year-old patient was admitted to the hospital due to “sudden upper abdominal pain and discomfort lasting for more than 1 day.” The issue began with epigastric pain and discomfort after consuming greasy food, leading to persistent bloating accompanied by nausea and vomiting of gastric contents. There were no chills or fever present. The patient initially sought treatment at the local county hospital, but symptomatic treatments there proved ineffective. Consequently, the patient and their family visited a local municipal tertiary hospital in an emergency. At the municipal hospital, it was recommended that the patient undergo a “laparoscopic cholecystectomy.” However, since the patient had undergone coronary stent implantation at the local county hospital on November 5, 2024, surgery was considered contraindicated. With acute severe cholecystitis symptoms worsening and pain relief efforts proving inadequate, the patient and family sought further treatment. After preoperative evaluations, the patient underwent a successful percutaneous transhepatic cholecystic puncture and drainage guided by color ultrasound. This procedure resulted in significant improvement in both abdominal pain and inflammatory markers.ConclusionFor patients undergoing surgical cardiac stent implantation, requiring prolonged anticoagulant therapy, and concurrently experiencing acute severe cholecystitis, percutaneous transhepatic gallbladder drainage (PTGD) is an effective treatment option.